1997
DOI: 10.1073/pnas.94.13.7094
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a mutant α-zein creates the floury 2 phenotype in transgenic maize

Abstract: The maize floury2 mutation results in the formation of a soft, starchy endosperm with a reduced amount of prolamin (zein) proteins and twice the lysine content of the wild type. The mutation is semidominant and is associated with small, irregularly shaped protein bodies, elevated levels of a 70-kDa chaperone in the endoplasmic reticulum, and a novel 24-kDa polypeptide in the zein fraction. The 24-kDa polypeptide is a precursor of a 22-kDa ␣-zein protein that is not properly processed. The defect is due to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 34 publications
2
90
0
Order By: Relevance
“…Therefore, we showed that the coding region of the mutant gene, which is tightly linked to the PB phenotype in sorghum P721Q, produces the same phenotype in maize as a gain of function. This also confirmed that as in floury2 in maize 20 , the compartmentalization of storage proteins in PBs is conserved between the two species.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, we showed that the coding region of the mutant gene, which is tightly linked to the PB phenotype in sorghum P721Q, produces the same phenotype in maize as a gain of function. This also confirmed that as in floury2 in maize 20 , the compartmentalization of storage proteins in PBs is conserved between the two species.…”
Section: Resultssupporting
confidence: 74%
“…Analogous to the sorghum phenotype, similar irregular and clumped PB morphologies in endosperm cells have previously been observed in two maize mutants with semi-dominant and dominant floury kernels [19][20][21] . These mutants resulted from point mutations at different sites in the ER signal peptides of a 22-kDa a-zein (floury2) and a 19-kDa a-zein (De-*B30).…”
mentioning
confidence: 80%
“…Several opaque mutants, e.g. floury2 (fl2) and Defective endosperm B30 (De-B30; Coleman et al, 1997;Kim et al, 2004a), are caused by defective signal peptides in a-zein proteins that disrupt protein body assembly (Zhang and Boston, 1992), leading to increased expression of genes involved in the unfolded protein response (Hunter et al, 2002). These observations are consistent with the hypothesis that the size, number, and structure of zein protein bodies influence the texture and vitreous phenotype of the mature endosperm (Coleman and Larkins, 1999).…”
supporting
confidence: 76%
“…In maize mutants, the increase in the precursor of storage protein, 22 kDa-alpha-zein, was observed in flo-2 (Coleman et al 1997) and the quantitative increase of a protein (34 kDa, pI = 5.57) and decrease of some proteins were shown in o2 (Damerval and Guilloux 1998). The quantitative difference of proteins observed between wild and mutant kernels of o2 and flo-2 were not detected between whitecore and non-white-core grains of rice.…”
Section: White-core-specific Proteinmentioning
confidence: 79%
“…In maize (Zea mays), it is reported that flo-2 mutant bore soft kernels with floury endosperm, and the kernels contained some proteins that were not detected in those of the wild type (Coleman et al 1995(Coleman et al , 1997. Damerval and Guilloux (1998) reported that novel proteins were synthesized in developing endosperm of opaque kernels of o2 mutant.…”
Section: Introductionmentioning
confidence: 99%